An open-label study to evaluate biomarkers and safety in systemic sclerosis patients treated with paquinimod - Hesselstrand, Roger; Distler, Jörg; Riemekasten, Gabriela; Wuttge, Dirk M.; Torngren, Marie; Nyhlen, Helen C.; Andersson, Fredrik; Eriksson, Helena; Sparre, Birgitta; Tuvesson, Helen; Distler, Oliver (Arthritis Research & Therapy, 2021)
Objectives: To evaluate the changes in disease-related biomarkers and safety of paquinimod, an oral immunomodulatory compound, in patients with systemic sclerosis (SSc). Methods: In this open-label, single-arm, multicenter study, SSc patients with a rapidly progressive disease received paquinimod for 8 weeks. Blood and skin biopsies were collected at baseline, during treatment, and at follow-up for the analyses of type I interferon (IFN) activity, chemokine (C-C motif) ligand 2 (CCL2), and the number of myofibroblasts. The safety of paquinimod was evaluated throughout the study. Results: Nine SSc patients were enrolled and completed the study treatment with paquinimod at 3 mg/day for 8 weeks. After the treatment, a reduction of type I IFN activity in the plasma from one patient with elevated baseline IFN activity was recorded. A trend towards reduced IFN activity in the skin after treatment was also observed in patients. The serum level of CCL2 was reduced in 7 of 9 patients after paquinimod treatment. There was a median reduction of 10% of the number of myofibroblasts in skin biopsies at week 8 compared to baseline. No change in modified Rodnan skin score and quality of life was detected in the study. Reported adverse events (AEs) were mild to moderate and expected with the most common being arthralgia (n = 3) and headache (n = 3), and C-reactive protein (CRP) increase. Conclusions: Analysis of biomarkers before and after treatment suggest reduced type I IFN activity and reduced number of myofibroblasts in lesional skin. Paquinimod was overall well tolerated with mild to moderate and expected AEs. Trial registration: ClinicalTrials.gov, NCT01487551. Registered on 7 September 2011.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Clinical trial; Paquinimod; Skin fibrosis; Systemic sclerosis